SMART TECHNOLOGY FOR ACCIDENT DETECTION AND MONITORING SYSTEM USING IOT - Nagajothi V.; Samritha. G; Ms. M. Muthumalathi (Galaxy International Interdisciplinary Research Journal, 2022)
The Accident detection and Monitoring system is to improve the road safety facilities and rescue operation system. Nowadays road accidents are very high due to drunk and drive and speed driving. To identify these factors with an automated response, our system is required. In this paper we introduce the Automatic accident detection and Alert system. This alert system technology sends the message to the authorized person to send the ambulance in case of accident. The system includes a MEMs sensor, Alarm and GSM module. The sensor will detect whether the two wheeler is normal or is in improper position and it monitors the accident and give alarm to authorized person through MEMs sensor. We can easily sense the condition of the vehicle and GSM will send notification. This paper helps to monitoring and detecting the accident places and send the alarm and notifications to authorized person for reduce the death caused of human.